Real-World Effectiveness of Oral Semaglutide in Indian Adult Diabetic Patients: Evaluation of EMR-based Data - Sandeep Gudibanda; Sharayu Govardhane; Supriya Kaloo; Snehal Shah; Vaibhav Miglani; Garima Verma (Journal of Diabetology)
Introduction: Diabetes is increasingly becoming a significant health concern globally, including in India, where its prevalence continues to increase. Being overweight often acts as a catalyst for developing diabetes, exacerbating the condition and increasing the risk of other serious health complications such as heart disease, kidney problems, and nerve damage. Peptide-based molecules like semaglutide have proved their efficacy in controlling glycated hemoglobin (HbA1c) levels and body weight in diabetic patients.